Development of an ExeLearning-based mathematics e-module featuring cloze activities: Proportion and direct proportion materials for 7th grade students - Melliawati, Melliawati; Prastowo, Aang Yudho; Azmi, Roma Doni (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to determine the validity, practicality, and effectiveness of eXeLearning-based mathematics learning e-modules containing cloze activities on proportion and direct proportion materials. The subjects of this study were 14 seventh-grade students from SMP N 1 in the Posek Islands. The type of research is R&D using the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. Data collection methods included questionnaires and tests. The validity test results from the material experts yielded a score of 80%, and the media experts' score was 90%, indicating that the developed e-module meets the valid criteria. The student practicality test results averaged 87%, and the teacher practicality test results averaged 90%. The effectiveness calculation using the n-gain score was 0.89, indicating high effectiveness. Based on the validation process, practicality test, and effectiveness test, the eXeLearning-based mathematics learning module containing cloze activities on proportion and direct proportion materials is declared valid, practical, and effective. The developed e-module can help students understand the material, making it suitable for seventh-grade junior high school students.